Developing Effective Media Relations for Your County Program: WC020/AEC339, rev. 6/2021 - Telg, Ricky; Lundy, Lisa (EDIS, 2021)
This publication provides an overview of how to develop effective media relations for your county program. Minor revision by Ricky Telg and Lisa Lundy. Published by the UF/IFAS Department of Agricultural Education and Communication; 5 pp.